Iron pyritization in shallow methane fields in sediments of the Ría de Vigo (NW Iberian Peninsula). (5th April 2020) - Ramírez-Pérez, A.M.; de Blas, E.; Otero, X.L.
Graphical abstract: Image 1 Highlights: Ría de Vigo show over-pyritization of Fe. Pyrite formation is limited by the exhaustion of reactive Fe in deep sediments. The presence of methane gas in the sediment increase the Fe pyritization.